Novel molecular markers for assessment of human embryo competence - Poli, M (2016)
In vitro fertilization treatments are responsible for 1-5% births in industrialized countries. The safest way to generate a pregnancy is to transfer a single embryo to the mother, reducing the likelihood of multiple gestations. Hence, in order to maximize the chance of success, it is extremely important that the embryo prioritised for transfer is the most capable within the cohort of embryos generated by the patient. Along with cytogenetic components, it has been suggested that embryo protein expression patterns may correlate with its ability to implant. However, embryo proteomics strategies have not been easy to harness mainly due to the complexity of the media the embryos are cultured in, and the low concentration of the proteins that are secreted. In this study, the use of the blastocentesis procedure, which allows the safe retrieval of embryo inner fluid (blastosol), was described. The use of the blasocoel fluid as a source of embryonic DNA for preimplantation genetic assessment was also investigated. From this highly purified embryonic sample, a comprehensive catalogue of proteins present in the human blastosol was generated using standard and custom- made mass spectrometry strategies. The embryonic origin of these proteins was validated by gene expression microarray and RNASeq analysis. These experiments also allowed the identification of differentially expressed genes in the first two cell lineages, the Inner Cell Mass and the Trophectoderm. Finally, a targeted proteomics strategy able to measure part of the previously described protein targets in single blastosol samples was employed. The correlation between the presence and abundance of proteins of interest in single blastosols and several biological characteristics of the embryo, including its chromosomal status, was assessed. These data are of major interest for the understanding of human embryo development. The validated embryo-derived protein catalogue and blastocyst gene expression profiles generated in this study, provides access to a thorough document for consultation in human embryology proteomics-based experiment design, paving the way to next-generation proteomic-based embryo assessment.